A Note on Constant Mean Curvature Foliations of Noncompact Riemannian Manifolds. (3rd August 2022) - Ilias, S.; Nelli, B.; Soret, M.
Abstract : We aimed to study constant mean curvature foliations of noncompact Riemannian manifolds, satisfying some geometric constraints. As a byproduct, we answer a question by M. P. do Carmo (see Introduction) about the leaves of such foliations.